2021
DOI: 10.1108/ijphm-04-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Does healthcare service quality affect outbound medical tourists’ satisfaction and loyalty? Experience from a developing country

Abstract: Purpose Poor quality of services in the health-care sector of the developing countries like Bangladesh forces affluent patients to seek advanced medical treatment from abroad. The purpose of this study is to explore the outbound medical tourists’ satisfaction and loyalty on the basis of the quality of the health-care service provided by foreign medical institutions. Design/methodology/approach The medical tourists from Bangladesh who have got medical services from Indian medical institutions were taken as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 81 publications
(127 reference statements)
3
21
0
Order By: Relevance
“…This states (There is a statistically significant effect of service quality on patient satisfaction), as increasing the quality of service by one unit leads to an increase in patient satisfaction by (0.284), an S.E (0.040) and a C.R (7.124), This verifies the third sub-validity, hypotheses and the findings of this hypothesis are congruent with the results of [66] and study [50].…”
Section: Sub-hypothesis IIIsupporting
confidence: 79%
See 2 more Smart Citations
“…This states (There is a statistically significant effect of service quality on patient satisfaction), as increasing the quality of service by one unit leads to an increase in patient satisfaction by (0.284), an S.E (0.040) and a C.R (7.124), This verifies the third sub-validity, hypotheses and the findings of this hypothesis are congruent with the results of [66] and study [50].…”
Section: Sub-hypothesis IIIsupporting
confidence: 79%
“…They are mentioned in Every single research , that deals with service quality from that date until now, in addition to the model (SERVPERF) prepared by [48], and other models of various research ers that are distinctive contributions to enriching the quality of service. Several relevant studies have shown the general implications or benefits of medical providers in general when they are interested in the quality of service, showing that there is a positive impact relationship between quality of service and patient satisfaction based on the results of the Study [49,50]. The higher the quality of service, the higher the service provider's performance index [51].…”
Section: Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] and [ 46 ], using a purposive sample of Bangladeshi medical tourists to India, showed that healthcare service quality positively influences medical tourists’ satisfaction, which in turn affects their loyalty, i.e., revisit intention and intention to recommend. However, the satisfaction and loyalty measured in the aforementioned studies were specific to the medical facility, not for the destination as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While previous research has investigated multiple areas within medical tourism, the majority of these studies have focused on first-time destination choice or visit intention [ 10 12 ], with only a limited number of research studies evaluating the revisit intentions of medical tourists [ 7 , 13 ]. Moreover, much of the previous research has used evaluations of the overall destination image instead of looking into specific components of the tourists’ post-visit destination image [ 14 ].…”
Section: Introductionmentioning
confidence: 99%